The correlation between leptin and highly sensitive C-reactive protein levels in obese children aged 9-15 years - Sarah M. Warouw; Suryani As'ad; Satriono Satriono (Indonesian Pediatric Society Publishing House, 2011)
Background Obesity is a low level and chronic inflammatory condition predominantly affecting white adipose tissue, where macrophage infiltration is found. Leptin is one of many molecules relating obesity to cardiovascular disease. Leptin can increase cytokine production in macrophages and monocytes, and increase oxidative stress on endothelial cells. Pro-inflammatory cytokines, in turn, may trigger the release of C-reactive protein. Objective To examine the correlation between leptin and hsCRP in obese children aged 9-15 years. Methods This cross-sectional study was done in Manado from May to December 2009, on elementary and junior high school children. Subjects were obese children aged 9-15 years, with nutritional status detennined by Body Mass Index and converted into z-score. Physical examination, blood pressure, and blood examinations for  fasting blood sugar (FBS), lipid profile, leptin, and hsCRP were perfonned. Data were analyzed with appropriate statistical methods. Results The mean leptin level in obese children was 34,009.2 pgiL (SD 18,224.79), higher than that of the control, 7,760.9 pgiL (SD 8,859.55) (P<0.0001). The mean hsCRP level in obese children was 3.6 mgiL (SD 3.60), higher than that of the control, 0.7 mgiL (SD 1.32) (<0.0001). There was a significant positive correlation between leptin and hsCRP levels in obese children (r 􀀁 0.355; P<0.0001). Conclusions There is significant positive correlation between leptin and hsCRP levels in obese children aged 9-15 years. Increased leptin and hsCRP levels indicate a low degree of chronic inflammation. Thus, intervention is needed to decrease the body weight of obese children.